Cochlear implantation: An assessment of quality and readability of web-based information aimed at patients. (November 2015) - Seymour, Nicky; Lakhani, Raj; Hartley, Benjamin; Cochrane, Lesley; Jephson, Christopher
Abstract : Objectives: Patients should have access to high-quality health information websites on which to base their decision-making. There are concerns regarding the accuracy and quality of some health websites. We aimed to objectively measure website quality related to cochlear implantation. Methods: Selected patient-information websites were scored, depending on how highly they ranked on search engines and if they were ranked on more than one of the search engines used. The top 40 websites from three major search engines were analysed. The quality of each website was scored using the DISCERN tool and the readability was scored using the Flesch–Kincaid reading ease and the Gunning-Fog index. Results: The average Flesch–Kincaid score was 49.7, giving an average reading age of a 15–17 years old, and the average Gunning-fog score was 13.1, which equals that of an 18 years old. Conclusion: Internet-based information regarding cochlear implantation is of varied quality and is written above the expected reading level of an average person.